2007
DOI: 10.1016/j.visres.2007.01.030
|View full text |Cite
|
Sign up to set email alerts
|

The path of least persistence: Object status mediates visual updating

Abstract: On what basis does the visual system use recently sampled information to update existing representations of the world? One possibility is that representations are updated through an image-based point-for-point replacement process. An alternative possibility is that representations are updated on the basis of perceptually organized units that reflect objects in the scene rather than locations within the visual field. We report a new effect involving a modulation of visible persistence that seems to support this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 36 publications
9
77
1
Order By: Relevance
“…It is assumed that when the visual system is faced with continuously changing information in the standing wave displays, it organizes the scene into a set of objects that are moving and changing over time. The idea is that the integration of newly sampled information into existing visual representations is mediated through the object representations that are formed through this organization process (e.g., Enns et al, 2008;Lleras & Moore, 2003;Moore & Lleras, 2005;Moore et al, 2007). To the extent that a stimulus is perceived as a later instantiation of an existing object within the current representation of the scene, that stimulus will be allowed to update that object representation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is assumed that when the visual system is faced with continuously changing information in the standing wave displays, it organizes the scene into a set of objects that are moving and changing over time. The idea is that the integration of newly sampled information into existing visual representations is mediated through the object representations that are formed through this organization process (e.g., Enns et al, 2008;Lleras & Moore, 2003;Moore & Lleras, 2005;Moore et al, 2007). To the extent that a stimulus is perceived as a later instantiation of an existing object within the current representation of the scene, that stimulus will be allowed to update that object representation.…”
Section: Resultsmentioning
confidence: 99%
“…As the central bar and mask become more dissimilar, they are less likely to be perceived as different instantiations of one object. As a consequence, the representation of the central bar is more likely to be protected from being overwritten by the surrounding rectangles (see also Moore & Enns, 2004;Moore et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Moore, Mordkoff, and Enns (2007) found that the perception of moving visual elements was influenced by (and influences) the background over which the object moves. It was therefore assumed that moving animated objects over existing visual elements on the screen could possibly interfere with accurate perception.…”
Section: Animation (Rn3)mentioning
confidence: 99%
“…The formation of a new object (object registration) will occur instead of updating of an existing object (object updating) as a direct consequence of the number and strength of cues present in an image signalling the likelihood of a new object. These cues include violations of spatial contiguity, geometric and chromatic similarity, and temporal simultaneity (Bennett, Lleras, Oriet, & Enns, 2007;Lleras & Enns, 2004;Moore et al, 2007). 2.…”
mentioning
confidence: 99%